2020
DOI: 10.3991/ijet.v15i10.13337
|View full text |Cite
|
Sign up to set email alerts
|

Linked Open Data Framework for Ethnic Groups in Thailand Learning

Abstract: The key significant worldview of the Semantic Web is Linked Open Data, another period of the World Wide Web that capacities to carry suggestions to information. An enormous number of both public and private foundations have dis-tributed their information following the Linked Open Data philosophies, or have done as such with information from different associations. To this degree, since the generation and production of Linked Open Data are thorough designing procedures that require high consideration so as to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This research is the continuation of former work [22][23][24], which organized knowledge and constructed the channel for exchanging information on the ethnic groups in Thailand in the form of ontology taxonomy and linked open data. This research differs from the previous work as demonstrated in Table 4, especially in the scope of knowledge that has been expanded to cover the ethnic groups in the Mekong River Basin and the thesaurus construction with broad terms, narrow terms, related terms, and vocabulary relationships as well as cross references.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This research is the continuation of former work [22][23][24], which organized knowledge and constructed the channel for exchanging information on the ethnic groups in Thailand in the form of ontology taxonomy and linked open data. This research differs from the previous work as demonstrated in Table 4, especially in the scope of knowledge that has been expanded to cover the ethnic groups in the Mekong River Basin and the thesaurus construction with broad terms, narrow terms, related terms, and vocabulary relationships as well as cross references.…”
Section: Discussionmentioning
confidence: 94%
“…The ethnic groups in Thailand have been divided into 12 classes and 51 subclasses [22,23]. Later, Chansanam et al [24], extended the finding by arranging the Thai ethnic groups ontology in an accessible form using linked open data technology. Categorization of ethnic groups in different countries in the Mekong Basin appears in the research by, for instance, Pholsena [25], who reported that the first Prime Minister of Lao PDR, Kaysone Phomvihane, changed the vocabulary and ethnic group classification in Lao PDR by dividing them into Lao-Thai, Mon-Khmer, Hmong-Mien, and Sino-Tibetan.…”
Section: Introductionmentioning
confidence: 99%
“…While [27] talk about creating ontologies, they also suggest using thesauri as a starting point. In this view, EGMRB Thesaurus employed knowledge structure [28] based on ethnicity in six countries, moreover utilized semantic data categorization using a LOD framework [25], expanding researchers' boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Additional anthropological thesauri and controlled vocabularies are necessary to the academic community. Furthermore, the EGMRB Thesaurus is utilized by the Linked Data system for data annotation [25]. When contributors uploading data resources through the portal utilize the data ingestion web interface, they must name their dataset's fields after the taxonomies, which are located inside the thesauri.…”
Section: Development Of the Egmrb Thesaurusmentioning
confidence: 99%
“…The advancement of new technologies and progressive social change has improved data production and sharing approaches, including simpler and greater access to information, mainly information services [4]. Modern technology enables enormous amounts of information from several domains to be gathered and processed.…”
Section: Literature Reviewmentioning
confidence: 99%